2012
DOI: 10.1039/c2cc31281f
|View full text |Cite
|
Sign up to set email alerts
|

CuproCleav-1, a first generation photocage for Cu+

Abstract: By utilizing thioether ligands, CuproCleav-1 stabilizes Cu(+) complexes in aqueous solution and releases the guest metal ion upon photolysis of the nitrobenzyl group. The photocage has an apparent K(d) of 54 pM for Cu(+), and metal ion release has been demonstrated using the fluorescent sensor CS1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…The o ‐nitrobenzyl system undergoes a photoreaction, yielding the release of the metal ion. Similar irreversible metal ion release has been shown for other o ‐nitrobenzyl caged compounds or by using light as a stimulus in conjugation with photosensitized singlet‐oxygen formation …”
Section: Chemical Communication Through Release Of Metal Cationssupporting
confidence: 69%
See 1 more Smart Citation
“…The o ‐nitrobenzyl system undergoes a photoreaction, yielding the release of the metal ion. Similar irreversible metal ion release has been shown for other o ‐nitrobenzyl caged compounds or by using light as a stimulus in conjugation with photosensitized singlet‐oxygen formation …”
Section: Chemical Communication Through Release Of Metal Cationssupporting
confidence: 69%
“…[11,39] The Zn 2 + source consisted of ac oordination complex with ap hotocleavable ligand system (15). The o-nitrobenzyl system undergoes ap hotoreaction,y ieldingt he releaseo ft he metal ion.S imilar irreversible metal ion release has been shown for other o-nitrobenzyl caged compounds [40,41] or by using light as as timulus in conjugation with photosensitized singletoxygenf ormation. [42] Notably,t he light-induced release of metal ions can be performed with reversibly operating systems.…”
Section: Chemical Communication Through Release Of Metal Cationsmentioning
confidence: 89%
“…14 The present review covers recent developments in the field, focusing on the scope, limitations, and applications of PPGs, which are used to release organic molecules. Photoactivation of small inorganic species and ions, such as NO, 15 CO, 16 Ca 2+ , 9h,17 Zn 2+ , 18 Cd 2+ , 19 or Cu + , 20 is not covered. Simplified basic structures of the photoremovable protecting groups discussed in this review are listed in Table 1 (the leaving groups are shown in red).…”
Section: Introductionmentioning
confidence: 99%
“…[11] Alternatively, photolytically breaking a carbon-heteroatom bond provides compounds that release metal ions through the reduction of chelate effects. The Cleav class of photocaged complexes can effectively buffer and release Ca 2+ , [13] Cu 2+/1+ , [14,15] or Zn 2+ depending on the ligand design. [16,17] Photocages based on oNB remain the dominant technology to study signal transduction mediated by biomolecules despite limitations like slow analyte-release kinetics, the requirement of UV light for photolysis and the formation of potentially toxic nitroso photoproducts.…”
mentioning
confidence: 99%